Degradation Characteristics of Wastewater Containing 2-Chlorophenol and 4-Chlorophenol Compounds, Using a Dielectric Barrier Discharge (DBD) Cold Plasma Reactor - Luvita, Veny; Sugiarto, Anto Tri; Bismo, Setijo (Instrumentasi, 2021)
Wastes containing phenolic compounds, including 2-chlorophenol and 4-chlorophenol at a threshold exceeding 50 mg / L, are very harmful to the environment. The processing of waste containing phenolic compounds using ozone and plasma technology is therefore an environmentally friendly and relatively inexpensive solution. The processing carried out in this study uses ozone plasma technology. Plasma is generated by high voltage transformator which is fed into electrodes wound on a reactor made of quartz glass. The reactor type is dielectric barrier discharge (DBD) have the ability to degrade these waste, by producing reactive oxygen species, including •OH, •O2- and molecular species of O3, H2O2. Subsequently, active species with high energy are transferred to the liquid phase, to react with chlorophenol compounds. According to the results, the dielectric barrier discharge plasma reactor using electrode coils was able to degrade waste containing 2-chlorophenol compounds by 70.96% and 79.41%, in acidic and alkaline conditions, respectively, while, 4-chlorophenol was degraded by 23.42% and 53.54%, in acidic and alkaline conditions, respectively.